2021
DOI: 10.3390/en14113065
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Caprock Tightness for CO2 Enhanced Oil Recovery and Sequestration: Case Study of a Depleted Oil and Gas Reservoir in Dolomite, Poland

Abstract: This study addresses the problem of geological structure tightness for the purposes of enhanced oil recovery with CO2 sequestration. For the first time in the history of Polish geological survey the advanced methods, practical assumptions, and quantitative results of detailed simulations were applied to study the geological structure of a domestic oil reservoir as a potential candidate for a combined enhanced oil recovery and CO2 sequestration project. An analysis of the structure sequestration capacity and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Building a geological model and (then) performing both analytical or numerical geomechanical multiscale assessment using data from a mechanical earth model [38,39] is considered to be the "gold standard" for sealing and stability evaluation of caprock and even the whole trap. However, for many gas reservoirs, the pressure and production information of the reservoir were mainly concerned with the early development of the gas reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Building a geological model and (then) performing both analytical or numerical geomechanical multiscale assessment using data from a mechanical earth model [38,39] is considered to be the "gold standard" for sealing and stability evaluation of caprock and even the whole trap. However, for many gas reservoirs, the pressure and production information of the reservoir were mainly concerned with the early development of the gas reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that there is a close correlation between the hydrogen concentration and hydrocarbon presence in oil and gas fields. (4) Salt rocks: Salt rocks are well-known cap rocks of oil and gas reservoirs [72]. Such evaporative formations may trap the natural hydrogen [73].…”
Section: Natural Hydrogen Detectionmentioning
confidence: 99%
“…Dynamic elastic properties were then recalculated to the static equivalents using the linear regressions developed in the previous studies dedicated to the main dolomite reservoir rock [74].…”
Section: Modeling Of Geomechanical Propertiesmentioning
confidence: 99%